1977
DOI: 10.1128/aem.34.4.355-362.1977
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-reducing bacterium from human feces

Abstract: An anaerobic, gram-positive diplobacillus that reduces cholesterol to coprostanol was isolated from human feces and rat cecal contents. The isolates closely resemble a cholesterol-reducing organism isolated by Eyssen et al. (H. Eyssen et al., Eur. J. Biochem. 36:412-421, 1973) from a rat's cecum. These organisms would not form colonies and were isolated and cultivated in an anaerobic medium containing homogenized pork brains (naturally high in cholesterol). These organisms require free or esterified cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 17 publications
1
32
0
1
Order By: Relevance
“…Sterols biotransformation by the gut microbiota has been widely studied by in vitro assays using microbiota from human, [18][19][20][21][22][23][24] rat, [25][26][27] pigeon, and chicken feces. [24] In addition, pure cultures of enteric microorganisms such as Eubacterium sp., [28][29][30][31][32][33][34] Clostridium perfringens, Bifidobacterium sp., Enterobacter aerogenes, [35] Escherichia coli, [35,36] Bacteroides sp. [37] have been used in order to study cholesterol metabolites.…”
Section: Dietary Sterols Biotransformation By Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Sterols biotransformation by the gut microbiota has been widely studied by in vitro assays using microbiota from human, [18][19][20][21][22][23][24] rat, [25][26][27] pigeon, and chicken feces. [24] In addition, pure cultures of enteric microorganisms such as Eubacterium sp., [28][29][30][31][32][33][34] Clostridium perfringens, Bifidobacterium sp., Enterobacter aerogenes, [35] Escherichia coli, [35,36] Bacteroides sp. [37] have been used in order to study cholesterol metabolites.…”
Section: Dietary Sterols Biotransformation By Gut Microbiotamentioning
confidence: 99%
“…In fact, some investigators have suggested that the cholesterol conversion rate is associated with microbial density, [37,57] mucosal receptors for coprostanoligenic fecal bacteria [58] or inhibition of these bacteria by other gut microbiota members. [31]…”
Section: Dietary Sterols Biotransformation By Gut Microbiotamentioning
confidence: 99%
“…coprostanol&enes and its cholesterol-reducing activity were recovered from the experimental group but not from the control group (data not shown). The presence of other indigenous coprostanol-producing bacteria in the digestive tracts of rabbits accounts for the relatively great coprostanol-to-cholesterol ratios in the contents of caecum and colon of the control group (Eyssen et al 1973;Sadzikowski et al 1977;Brinkley et al 1982). These bacteria, however, exert little if any effects on cholesterol absorption because cholesterol absorption takes place primarily in the small intestine and not in the caecum and colon (Gotto et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Coprostanol, a saturated product of cholesterol, is absorbed poorly from the gastrointestinal system (Bhattacharyya 1986). Cholesterolreducing bacteria have been isolated from faeces of rats (Eyssen et al 1973), humans (Sadzikowski et al 1977) and baboons (Brinkley et al 1982). Most of these previously isolated bacteria were difficult to grow in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…A few strictly anaerobic bacteria have been associated with the reduction of cholesterol to coprostanol. They have been classified mostly within the Eubacterium genus (Eyssen et al, 1973;Sadzikowski et al, 1977;Freier et al, 1994). To the best of our knowledge, E. coli has never been associated with the intestinal metabolism of cholesterol.…”
Section: Conversion Of Cholesterol To Coprostanolmentioning
confidence: 99%